2019
DOI: 10.31234/osf.io/d3xmf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality Change: Longitudinal Self-Other Agreement and Convergence With Retrospective-Reports

Abstract: The research literature on personality development is based mostly on self-report studies and on samples in younger adulthood. The present multi-method study examines self-other agreement on longitudinal personality change and convergence between self-and informant-reports of longitudinal and retrospective personality change in older adulthood. It provides a rare validation test of longitudinal measurements of personality change. A representative community sample of 1,630 older adults (M age = 62.5) and their … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Lastly, Study 2 revealed evidence that perceived and actual R/S growth are only modestly positively related. This finding is consistent with similar existing research on personality change more broadly (Oltmanns et al, 2019; Robins et al, 2005) and on attachment patterns (Kirkpatrick & Hazan, 1994). Taken together, retrospective measurement of personality change may tend to have limited value, because people are generally not very accurate in tracking their own change.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lastly, Study 2 revealed evidence that perceived and actual R/S growth are only modestly positively related. This finding is consistent with similar existing research on personality change more broadly (Oltmanns et al, 2019; Robins et al, 2005) and on attachment patterns (Kirkpatrick & Hazan, 1994). Taken together, retrospective measurement of personality change may tend to have limited value, because people are generally not very accurate in tracking their own change.…”
Section: Discussionsupporting
confidence: 92%
“…There was a weak correlation ( r = .22) between perceived PTG (PTGI scores at Time 2 [T2; posttrauma]) and actual change in C‐PTGI scores from Time 1 (T1; pretrauma) to T2. Those results corroborated the modest link that has been found between actual and perceived change in people's personality traits (Oltmanns, Jackson, & Oltmanns, 2019; Robins, Noftle, Trzesniewski, & Roberts, 2005) and attachment patterns (Kirkpatrick & Hazan, 1994). In their examination of convergence between perceived PTG and pre‐ to posttrauma changes in measures of each PTG domain (more likely reflecting actual PTG), Frazier et al (2009) found perceived PTG was only related to change in religious commitment ( r = .29); it was unrelated to change in the other four PTG domains.…”
Section: Introductionsupporting
confidence: 77%
“…Traits are reliable predictors of work outcomes, including occupational choice (Denissen, Ulferts, Lüdtke, Muck, & Gerstorf, 2014), job performance (Dudley, Orvis, Lebiecki, & Cortina, 2006), leadership (Judge, Bono, Ilies, & Gerhardt, 2002), income (Denissen et al, 2018), and occupational attainment (Roberts et al, 2007). There is also a large body of evidence highlighting the role of personality traits in predicting romantic relationship outcomes and marital trajectories (Asendorpf, Penke, & Back, 2011; Luciano & Orth, 2017; Neyer & Lehnart, 2007; Malouff, Thorsteinsson, Schutte, Bhullar, & Rooke, 2010; Roberts et al, 2007, Wagner, Becker, Lüdtke, & Trautwein, 2015); friendship, popularity, and status in peer relations (Anderson, John, Keltner, & Kring, 2001; Back, Schmukle, & Egloff, 2011; Selfhout et al, 2010; Stopfer, Egloff, Nestler, & Back, 2013); and subjective well–being and overall functioning (Bleidorn et al, in press; Lucas & Diener, 2015; Mueller, Wagner, Wagner, Ram, & Gerstorf, 2019).…”
Section: Why Should We Care About Personality Change?mentioning
confidence: 99%
“…In this respect, a central issue concerns the possibility of personality change throughout life. The APM proposes personality to be resistant to change, but empirical findings underpinned by the FFM indicate that changes are to be expected (Lucas and Donnellan, 2011;Oltmanns et al, 2019). For example, agreeableness and conscientiousness have been found to increase between age 20 and 60, while openness to decrease after 60, with important individual differences (Roberts and Mroczek, 2008).…”
Section: Implications For Personalitymentioning
confidence: 99%